¿Por qué son ineficientes las empresas estatales ecuatorianas? - Campaña , Isaías (1989)
This article was scanned by the Aurelio Espinosa Polit Ecuadorian Library.In recent times the State has been assuming an increasingly important role in the economy, greater emphasis was given to the planning of economic variables, the budget allocated to social spending and the provision of infrastructure and services necessary for the evolution of the economy expanded dizzyingly; especially since the 1970s, dozens of state and mixed companies began to operate, considering that they were the engine of the country's economic development.